DAMPAK PEMBANGUNAN EMBUNG BAGI USAHA TANI PADI SAWAH TADAH HUJAN - Dangnga, Muhammad Siri; Halimah, Andi S.; Asniar, A (Journal Galung Tropika, 2019)
Embung or reservoir is a building that serves to collect rain water and used in the dry season for farmers who manage rainfed lowland farming. This study aims to determine the impact of embung on rainfed lowland rice farming in Sanjai Village, East Sinjai District, Sinjai Regency, South Sulawesi, Indonesia. The study was descriptive qualitative, using questionnaires and depth interviews to obtain information about the impact of development and the use of reservoirs from physical, environmental, economic, socio-cultural, and institutional aspects. The results showed the social impacts of development and utilization of embungs generally had a positive impact on rainfed lowland rice farming. This impact was assessed from various aspects including physical, economic, socio-cultural and institutional aspects. It’s were directly proportional to the welfare of the farmers.